Immunoperoxidase study of the secretory immunoglobulin system and lysozyme in normal and diseased gastric mucosa. Issue 7 (July 1982) - Isaacson, P
Abstract : Using an immunoperoxidase technique the distribution of secretory component, IgA, and lysozyme has been investigated in normal, inflamed, dysplastic, and carcinomatous gastric mucosa. Apart from pyloric glands which contain lysozyme, normal gastric mucosa stains negatively for all three antigens. In gastric mucosa neck cells appear to adapt by synthesising secretory component and lysozyme and transporting IgA. Intense staining for the three antigens is seen in dysplastic gastric epithelium and in well-differentiated intestinal type carcinomas. With progressive de-differentiation the tumours lose the ability to synthesise secretory component and lysozyme. Carcinomas of the diffuse type stain positively for secretory component and lysozyme and individual cells appear to take up IgA even in the absence of surrounding IgA containing plasma cells. These functional properties are retained in lymph node metastases. It is suggested that secretory component synthesising malignant cells might take up circulating dimeric IgA and that this could be a reflection of an important physiological mechanism.